Persepsi Guru PJOK dan Guru Kelas terhadap Kolaborasi dalam Proyek Profil Pelajar Pancasila Bertema Gaya Hidup Berkelanjutan - Dwiky Novaldi Ramdhani; Alipia Oktapiani; Neng Hilma Paujiah; Novi Nurhopipah; Zulia Latifah; Rismawati Nurapipah; Alin Nurliana; Rahmat Permana (Jurnal Pendidikan Dirgantara, 2025)
This study aims to explore the perspective of Physical Education, Sports, and Health (PJOK) teachers and classroom teachers regarding the form and effectiveness of cooperation in the implementation of the Pancasila Student Profile Strengthening Project (P5) with the topic of Sustainable Lifestyle at Pajajaran State Elementary School. The implementation of the Independent Curriculum emphasizes the importance of collaborative, comprehensive, and contextual learning, where synergy between teachers is the main foundation for the success of thematic projects. This collaboration is essential to ensure that learning not only develops cognitive aspects, but also forms character and environmental awareness in students. The research method used is a qualitative approach with data collection techniques through semi-structured interviews, direct observation during the learning process, and document analysis such as learning implementation plans and P5 project reports. The data was analyzed with the stages of data reduction, data presentation, and conclusion drawing to obtain a comprehensive picture of the teacher's collaboration strategy. PJOK teachers play a role in field practice, such as teaching physical activities that prioritize the principles of sustainability and healthy living habits. Meanwhile, classroom teachers emphasized strengthening conceptual material on sustainability through discussions, literacy, and creative projects. The results of the study show that the synergy between PJOK teachers and classroom teachers creates more effective and meaningful learning. Challenges that arise include limited time for coordination, differences in teaching styles, and lack of a comprehensive understanding of sustainability concepts. However, motivation, commitment, and good communication are key factors to overcome these obstacles. This research emphasizes that teacher collaboration is crucial in supporting the successful implementation of the Independent Curriculum, while instilling the values of environmental care, independence, and social responsibility in students.